DETERMINING PERMISSIBLE SPEED OF TILTING TRAIN IN CURVED TRACK - Kapitsa, M. I.; Bobyr, D. V.; Desiak, A. Y. (Science and Transport Progress, 2017)
Purpose. The main purpose of the article is to determine the permissible speed of the air-cushioned tilting train in curved track and to justify the expediency of operating this type of rolling stock on the railways of Ukraine to increase the speed, improve the passenger comfort and save the energy due to more uniform high-speed train driving.Methodology. The determination of the maximum permissible speed of the tilted train in curved track involves the use of methods of linear and vector algebra and empirical formulas for applied scientific and technical research. The calculation of the maximum speed is based on the principle of calculating centrifugal force for the velocities that meet the safety criteria of movement on the horizontal unbalanced acceleration in the stable radius curve. Findings.The results of the calculations showed that in the 1000 m radius curved track section, provided the passenger comfort, the maximum permissible speed of the train without forced tilt is 132 km/h, and with the forced tilt – 189 km/h. The velocity gain in the curve is about 30% and up to 10% on the section (depending on the number of curves). Originality.The method of determining the permissible speed of the tilted train in curved track is improved, which consists in determining the permissible centrifugal force acting on the train in the stable radius curve, taking into account the passenger comfort conditions. Practical value.This method allows accurately determining the permissible speed on the condition of passenger comfort in the curved section and the required additional tilt angle of the train, depending on the speed, curve radius and canting. Enhanced speed and comfort of passenger trains in the future will increase the demand for rail services among the population and strengthen the position of rail transport in Ukraine’s transport system.